The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1071/pp9760721
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Acid Proteinase Activity and Redistribution of Nitrogen During Grain Development in Wheat

Abstract: Accumulation of grain nitrogen was studied in the wheat cultivars Argentine IX and Insignia. The pattern of nitrogen removal from several tissues of each cultivar was compared with the pattern of acid proteinase activity. There was a highly significant relation between the rate of nitrogen loss from the tissues and the rate estimated from the enzyme activity measurements. This suggests an important role for acid proteinase enzymes in leaf senescence. Redistribution of nitrogen present in the plant at anthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
71
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 26 publications
5
71
1
Order By: Relevance
“…Proteolysis during leaf senescence could be regulated by the appearance of new proteinases responsible for the hydrolysis of the leaf proteins in the same way that proteolysis in the storage tissues of young seedlings is regulated (1,2,8,9). Such a regulatory mechanism may exist in corn (5) and wheat (3,14) leaves where increases in proteinase activity accompany leaf senescence. Dalling et al (3) showed that there is a linear relationship between the acid proteinase activity measured with calculated rate of nitrogen loss from senescing wheat organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolysis during leaf senescence could be regulated by the appearance of new proteinases responsible for the hydrolysis of the leaf proteins in the same way that proteolysis in the storage tissues of young seedlings is regulated (1,2,8,9). Such a regulatory mechanism may exist in corn (5) and wheat (3,14) leaves where increases in proteinase activity accompany leaf senescence. Dalling et al (3) showed that there is a linear relationship between the acid proteinase activity measured with calculated rate of nitrogen loss from senescing wheat organs.…”
mentioning
confidence: 99%
“…Such a regulatory mechanism may exist in corn (5) and wheat (3,14) leaves where increases in proteinase activity accompany leaf senescence. Dalling et al (3) showed that there is a linear relationship between the acid proteinase activity measured with calculated rate of nitrogen loss from senescing wheat organs. Proteolysis could also be regulated by changing the accessibility of existing leaf proteases to leaf proteins.…”
mentioning
confidence: 99%
“…The rate of nitrogen depletion from the vegetative parts of the plants is fairly constant as long as the nitrogen concentration in the tissue is above a threshold level of around 0.01 kg kg-1 (Dalling, Boland & Wilson, 1976). Such a constant rate of depletion can be explained as withdrawal from a pool of amino-acids that is maintained at a more or less constant level, when calculated on an integrated daily basis (Hanson & Ritz, 1983).…”
Section: Translocation Of Nitrogen To the Seedmentioning
confidence: 99%
“…As the concentration of nitrogen in the vegetative parts approaches the residual level the rate of depletion drops (Dalling et al, 1976). The rate of transfer from the vegetative tissue and the uptake rate by the seeds are both dependent on temperature with a Q10 value of around 2 (Vos, 1981).…”
Section: Translocation Of Nitrogen To the Seedmentioning
confidence: 99%
See 1 more Smart Citation